Aux/IAA gene family identification and analysis reveals roles in flower opening and abiotic stress response in Osmanthus fragrans - Shanshan Cao; Yong Ye; Zifei Zheng; Shiwei Zhong; Yiguang Wang; Zheng Xiao; Qiu Fang; Jinping Deng; Hongbo Zhao; Bin Dong (Ornamental Plant Research)
The Aux/IAA (auxin/indole-3-acetic acid) gene family plays a crucial role in regulating various aspects of plant growth, development, and abiotic tolerance in the auxin transduction pathway. However, limited information is available about the Aux/IAA family in Osmanthus fragrans. This study aims to comprehensively analyze the Aux/IAA gene family on a genome-wide scale. A total of 39 OfIAA genes containing four conserved domains were identified. These genes were unevenly distributed across 19 chromosomes and grouped into six clades based on phylogenetic analysis, showing conserved gene structure and motif composition. The expansion of OfIAA genes in the O. fragrans genome was partially due to segmental duplication events. Analysis of cis-regulatory elements (CREs) in the promoters of the OfIAA genes revealed the presence of many CREs related to different hormones and abiotic stresses. Through transcriptome and expression pattern analysis, we found that the majority of OfIAA genes were expressed in the stem tissue. Moreover, during the flower opening process, 18 OfIAA genes exhibited differential expression, while three and 11 OfIAA genes, respectively, showed altered expression patterns after salt and drought treatments. These differentially expressed genes are likely involved in the regulation of flower opening and abiotic stress response. This study provides new insights into the potential roles of OfIAAs and contributes to a better understanding of the regulatory mechanisms of flower opening and abiotic stress tolerance in O. fragrans.